Correlation of Glasgow Coma Scale Score at Hospital Admission with Stroke Hemorrhagic Patient Mortality at Hasan Sadikin Hospital - Hartanto, Ary Setio; Basuki, Andi; Juli, Cep (Universitas Kristen Maranatha, 2019)
Stroke is the most common cause of death in Indonesia. Stroke is divided into ischemic and hemorrhagic stroke. Hemorrhagic stroke has a higher risk of death than ischemic stroke. Hemorrhagic stroke can disrupt patient’s consciousness. The Glasgow Coma Scale (GCS) is a scale that is widely used to assess level of consciousness. Accurate predictors can help doctors determine prognosis and treatment for stroke patient. This study was conducted to determine the correlation of GCS scores at the time of hospital admission and mortality of hemorrhagic stroke patients at Hasan Sadikin Hospital. This study is a retrospective cohort analytic study involving 134 subjects. Data were analyzed using Kolmogorov-Smirnov’s and Fisher's analysis test with significance of p <0.05. From the results of the study, the p value was 0.00, subjects with GCS score somnolence (12-14) had six times higher risk in mortality (P = 0.02, RR = 6.38) and subjects with GCS score sopor and coma (3 - 11) had twenty four times higher risk in mortality (P = 0.00, RR = 23.85). We concluded that decreased score of SKG at the time of hospital admission was associated with increased risk of death in hemorrhagic stroke patients at Hasan Sadikin Hospital. Keywords: Glasgow Coma Scale, hemorrhagic stroke, mortality